2016
DOI: 10.2214/ajr.15.15617
|View full text |Cite
|
Sign up to set email alerts
|

Free-Breathing Radial 3D Fat-Suppressed T1-Weighted Gradient-Echo Sequence for Contrast-Enhanced Pediatric Spinal Imaging: Comparison With T1-Weighted Turbo Spin-Echo Sequence

Abstract: For pediatric spinal imaging, radial VIBE images had better image quality and lesion conspicuity and fewer CSF and respiratory motion artifacts than did T1-weighted TSE images in a similar acquisition time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Axial 3D volume-interpolated gradient recalled echo sequences (ie, volume interpolated breathhold examination [VIBE]/ liver acquisition with volume acceleration [LAVA]/T1 high resolution isotropic volume excitation [THRIVE]) provide excellent resolution with minimal CSF pulsation artifacts. 22 For 2D SE techniques, the image order acquisition should be consecutive, not interleaved (as explained above in the "Brain Imaging" section); interleaved acquisitions are sometimes degraded by prominent CSF pulsation artifacts and therefore their routine use is not recommended. Maximum image thickness should be 4 mm (5 mm for larger patients).…”
Section: Spine Imagingmentioning
confidence: 99%
“…Axial 3D volume-interpolated gradient recalled echo sequences (ie, volume interpolated breathhold examination [VIBE]/ liver acquisition with volume acceleration [LAVA]/T1 high resolution isotropic volume excitation [THRIVE]) provide excellent resolution with minimal CSF pulsation artifacts. 22 For 2D SE techniques, the image order acquisition should be consecutive, not interleaved (as explained above in the "Brain Imaging" section); interleaved acquisitions are sometimes degraded by prominent CSF pulsation artifacts and therefore their routine use is not recommended. Maximum image thickness should be 4 mm (5 mm for larger patients).…”
Section: Spine Imagingmentioning
confidence: 99%
“…However, optimal abdominal MRI remains challenging in children, because sedated children in the free-breathing state during the MR exam have shallow, rapid, and sometimes irregular respiratory cycles, whereas non-sedated children are frequently unable to breath-hold for the required length of time. The stack-of-stars acquisition technique is a free-breathing method that can provide distortion-free images by in-plane radial and through-plane cartesian acquisition, both in 3D gradient echo body imaging and spine, head, and neck imaging (15,18). Comparisons of abdominal contrast-enhanced 3D GRE T1W imaging with free-breathing radial acquisition and breath-hold conventional Cartesian acquisition techniques showed that the former provided better quality images and was better able to identify lesions in pediatric patients (8,9) and in adults who have difficulty holding their breath (19).…”
Section: Discussionmentioning
confidence: 99%
“…The mean and SD of signal intensity within each ROI were measured, and the coefficient of variation was calculated by dividing the SD by the mean. The image quality of the three sequences was compared quantitatively by comparing the mean coefficients of variation calculated by the two reviewers (15).…”
Section: Methodsmentioning
confidence: 99%
“…T1-weighted 3D techniques for the spine have shown comparable or superior image quality to 2D techniques. 34,35 The multiplanar reformatting capability of 3D scans can significantly speed total acquisition time of a contrast-enhanced study where one or more T1-weighted sequences are separately acquired with 2D techniques.…”
Section: T1-weighted Fast Spin Echomentioning
confidence: 99%